Uma genealogia do jovem usuário de crack: mídia, justiça, saúde, educação - Oliveira, Douglas Casarotto de (2009)
This paper is about a genealogy of a young crack user in the city of Santa Maria, Rio Grande do Sul. In this way the notions are thought with universal pretentions which affect the young user of crack. It aims at movement production in discussions about this issue, giving emphasis to problematizing perspectives generated from educational field. This theme choice has come to since composition taken as professional experience of the researcher as the manager of Mental Health Politics of Santa Maria, and discussions and also approaches done to the Moral Affection Group Research, linked to the Post Graduation in Education Program at the Federal University of Santa Maria (UFSM), focused on violence theme and conflicts related to education. This investigation is based on genealogical perspective, grounding in Michel Foucault thoughts. The materials used were documents relative to an adolescent situation involved with the crack drug, this young L., collected in the Regional Judge of Infant and Adolescent of Santa Maria, to the health service in the city which attend users of crack, as well as news on a local newspaper which followed up his situation. As its way of genealogical analysis, these materials, along with other productions about the theme, were taken as Foucault suggests, as dispersal, a way of reducing the effects of hierarchy of research sources and their speeches. For that, they are considerated drugs and the hegemonic status of forbidden politics to that associated from legal-police and medical-psychiatrist axes. It is questioned about potency of practices to be constituted from education field as an exclusive way of putting in action a politics/pedagogy based on aspects besides prohibition. Thus, this research was upon the problematizing views of practices from hegemonic knowledge which act producing the notion of young user of crack, and it has made possible the creation of places for education rising as its autonomous field to this knowledge.